2014
DOI: 10.3855/jidc.3277
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical-induced reduction of pulmonary inflammation during Klebsiella pneumoniae lung infection in mice

Abstract: Introduction: Curcumin, a polyphenol derived from the herb Curcuma longa, has number of antioxidant, anti-inflammatory, antimicrobial, and anti-carcinogenic activities. Its anti-inflammatory property was here studied alone and in combination with clarithromycin in a mouse model of acute inflammation. Methodology: A total of 80 mice divided into four groups were used. Mice receiving curcumin and/or clarithromycin were fed orally with curcumin (150 mg/kg/day) for 15 days prior to infection, whereas clarithromyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In this study, mice that received orally curcumin alone or in combination with augmentin showed a significant decrease in neutrophil influx into the lungs and a significant decrease in the production of NO, MPO activity and TNF-α levels [ 86 ]. Similar results have been obtained by combining curcumin and clarithromycin [ 87 ]. Kim et al evaluated also the effects of a dietary supplementation with turmeric on systemic and local immune responses on experimental Eimeria maxima and Eimeria tenella infections in commercial broiler chickens [ 88 ].…”
Section: Curcuma Longasupporting
confidence: 86%
“…In this study, mice that received orally curcumin alone or in combination with augmentin showed a significant decrease in neutrophil influx into the lungs and a significant decrease in the production of NO, MPO activity and TNF-α levels [ 86 ]. Similar results have been obtained by combining curcumin and clarithromycin [ 87 ]. Kim et al evaluated also the effects of a dietary supplementation with turmeric on systemic and local immune responses on experimental Eimeria maxima and Eimeria tenella infections in commercial broiler chickens [ 88 ].…”
Section: Curcuma Longasupporting
confidence: 86%
“…For the pneumonia model, mice were anesthetized and inoculated intra-nasally with irradiated ATCC27853 cells to further evaluate the protective effect generated by the vaccine 43 . Briefly, mice were immunized by placing 20 μl of the vaccine inoculums into each nasal (40 μl per mouse totally).…”
Section: Methodsmentioning
confidence: 99%
“…Of the 10 publications, which evaluated the therapeutic efficacy of curcumin on pneumonia or acute lung injury/acute respiratory distress syndrome (ALI/ARDS) in vivo, 7 studies used bacteria to generate the mouse model of the diseases, whereas 3 studies used viruses for this purpose. Four studies used S. aureus to generate a mouse model of pneumonia (Wang et al, 2016; Xu et al, 2015, 2016; Ye et al, 2014), 3 studies used K. pneumoniae (Bansal & Chhibber, 2010, 2014; Zhang et al, 2019), 2 studies used Influenza A virus (IAV) (Han et al, 2018; Dai et al, 2018) and one study generated the mouse model using infection with reovirus 1/L (Avasarala et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…For generating pneumonia mouse models, four studies used C57BL/6 mice (Dai et al, 2018; Wang et al, 2016; Xu et al, 2015; Zhang et al, 2019), three studies used BALB/c mice (Bansal & Chhibber, 2010, 2014; Han et al, 2018), one study used CBA/J (Avasarala et al, 2013), one study used FVB/N (Xu et al, 2016) and one study used Kunming mice (Ye et al, 2014). Four studies only used female mice (Avasarala et al, 2013; Han et al, 2018; Wang et al, 2016; Xu et al, 2015) while the other studies used both male and female mice (Bansal & Chhibber, 2010, 2014; Dai et al, 2018; Xu et al, 2016; Ye et al, 2014; Zhang et al, 2019). The mice were subcutaneously injected with curcumin at doses 10–150 mg/kg/day from 15 days before the intranasal inoculation of viruses or bacteria to several hours after the inoculation, depending on the study.…”
Section: Resultsmentioning
confidence: 99%